Myalgic encephalomyelitis/chronic fatigue syndrome patients' reports of symptom changes following cognitive behavioural therapy, graded exercise therapy and pacing treatments: Analysis of a primary survey compared with secondary surveys. (September 2019) - Geraghty, Keith; Hann, Mark; Kurtev, Stoyan
Cognitive behavioural therapy and graded exercise therapy are promoted as evidence-based treatments for myalgic encephalomyelitis/chronic fatigue syndrome. This article explores patients' symptom responses following these treatments versus pacing therapy, an approach favoured by many sufferers. We analyse data from a large cross-sectional patient survey ( n  = 1428) and compare our findings with those from comparable patient surveys ( n  = 16, 665), using a mix of descriptive statistics and regression analysis modelling. Findings from analysis of primary and secondary surveys suggest that cognitive behavioural therapy is of benefit to a small percentage of patients (8%–35%), graded exercise therapy brings about large negative responses in patients (54%–74%), while pacing is the most favoured treatment with the lowest negative response rate and the highest reported benefit (44%–82%).